Relación del entorno social en la conducta de los niños de educación inicial de 4 a 5 años del Centro Educativo 9 de Mayo. - Lupercio Tacuri, Ana Lucia (2015)
His research was applied to determine the impact that the social environment in the development of significant learning from the perspective analyzing the actions of teachers to the process of developing meaningful learning the nuances of developing seminar workshop for teachers to to improve the quality of education, care and student performance.